The influence of angiotensin II on sex-dependent proliferation of aortic VSMC isolated from SHR - Loukotová, J; Bacáková, L; Zicha, J; Kunes, J (Physiological research, 1998)
The growth response to angiotensin II (Ang II) was studied using cultured vascular smooth muscle cells (VSMC) isolated from the aortae of male and female spontaneously hypertensive rats (SHR). Systolic and mean arterial blood pressure of 10-week-old males was significantly higher when compared to age-matched females. The specific growth rate of male VSMC was significantly higher on the third and sixth day after synchronisation. Angiotensin II in concentration 10(-7) M stimulated the specific growth rate only in male VSMC during the exponential phase of growth. Moreover, doubling time was 3 hours shorter in male VSMC in comparison with the females. Our results suggest that both the increased specific growth rate and augmented growth-response of male VSMC to Ang II may explain the higher sensitivity of males to hypertensive stimuli.
Keywords: kultivované buňky; Rats; angiotensin II; krevní tlak; Hypertension; Aorta; buněčné dělení; mužské pohlaví; aorta; potkani inbrední SHR; Cell Division; krysa rodu Rattus; systola; svaly hladké cévní; Muscle, Smooth, Vascular; Cells, Cultured; ženské pohlaví; zvířata; Blood Pressure; Sex Characteristics; Angiotensin II; hypertenze; Rats, Inbred SHR; pohlavní dimorfismus; Female; Systole; Male; Animals